The power of learning from the bottom up: working towards a blueprint for community-led biodiversity protection and restoration - Emma Verling; Maria Power; Melanie Biausque; Lee Wah Pay; Aoife Deane; Rory Scarrott; Darragh Ó Súilleabháin (Cambridge Prisms: Coastal Futures, 2025)
The impacts of climate change have become more widespread and frequent, and society is beginning to recognise the connection between it and the biodiversity crisis. Communities have the capacity to play a key role in the success of multi-stakeholder nature restoration projects, but examples of successful projects, in which communities are the architects of the action – as opposed to the recipients of it – are not well documented. This study used a participatory evaluation research approach to explore a multi-stakeholder, community-led restoration project at Harper’s Island Wetlands, Co. Cork, Ireland to understand the elements of success and to extract key learnings for other communities. In order to rapidly upscale nature restoration and biodiversity protection globally, there is an urgent need to gain speed and momentum, identifying innovative approaches and disseminating them appropriately. The insights from this case study highlight four key components to be considered by groups at the beginning of community-led projects: setting up a core committee, assigning clear roles within the committee, creating a short-, medium- and long-term strategy and beginning practical tasks as soon as possible. This research serves as a step towards preparing blueprints to inform research, policy and practice in this space to enable stakeholders to respond collectively